Performance of Dichrostachys nutans and Leucaena leucocephala Based Agroforestry System in Arid Rajasthan - Sharma, N. K. (Indian Forester, 2015)
erformance of two woody perennials Dichrostachys nutans and Leucaena leucocephala and five seasonal rabi crops viz., isabgol (Plantago ovata), cumin (Cuminum cyminum), fenugreek (Trigonella foenum-graecum), asaliya (Lepidium sativum) and taramira (Eruca sativa) was studied under agroforestry system at Agricultural Research Station, Keshwana, Jalore (Rajasthan). Woody perennials were planted at 5.0m x 1.0m spacing. Seasonal crops were sown between two rows of woody perennials. Dichrostachys nutans attained a plant height of 280 cm and provided 100.6 q/ha green fodder leaves and 180.6 q/ha fuel wood with 93.5 per cent survival after 8 years of plantation. However, Leucaena leucocephala attained a height of 498 cm with 71.2 q green fodder leaves and 201.6 q/ha fuel wood with 86.9 per cent survival after 6 year. Seed yield of all five intercrops recorded under agroforestry system was lower than the open field. The levels of yield reductions of seasonal crops were higher under L. leucocephala based agroforestry system.